Influence of polyacrylic acid (PAA)/Na2HPO4 mixture on biphasic calcium phosphate cement: Enhancing strength and cell viability. Issue 4 (27th April 2021) - Thaitalay, Paritat; Thongsri, Oranich; Dangviriyakul, Rawee; Srisuwan, Sawitri; Talabnin, Chutima; Suksaweang, Sanong; Srakaew, Nuan La‐ong; Rattanachan, Sirirat Tubsungnoen
Abstract: This study has investigated the effect of combination of new liquid phase mixture of disodium hydrogen phosphate (Na2 HPO4 ) and polyacrylic acid (PAA) on the compressive strength, setting time, bioactivity, and cytotoxicity of biphasic calcium phosphate cement. The PAA was known as one of water‐soluble and biocompatible polymers to improve the mechanical performances of the bone cement, but it usually inhibits the phase conversion to hydroxyapatite after the cement has already set. The aim of this work was to evaluate the incorporation of the mixture of PAA and Na2 HPO4 into biphasic cement. We have found the crucial concentration for adding PAA/Na2 HPO4 at 30:70 v/v% to enhance the mechanical strength, cell viability, and maintain bioactivity. The phase composition and crosslinking reaction between PAA and alpha‐tricalcium phosphate (α‐TCP) powder were detected by XRD and FTIR techniques. The beta‐tricalcium phosphate (β‐TCP) was added in the formula to achieve the biphasic cement, which composed of β‐TCP and apatite/calcium deficient‐hydroxyapatite (CD‐HA) in the final product. The biphasic granule commercial product was used as comparison in the cell viability test. This work had been confirmed that the cement was a nontoxic material. Therefore, our results suggest that the PAA/Na2 HPO4 could be beneficial for further clinical applications.